2022
DOI: 10.55489/njcm.130720221268
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study on Assessment of Cognitive Impairment and Behavioural Risk Factors Among Senior Citizens Living in Old Age Homes in Chengalpattu District, Tamilnadu

Abstract: Background: Ageing is an irreversible, unavoidable, universal phenomenon accompanied by gradual reduction in functional capacity of the elderly. The number of elderly populations in India is expected to triple reaching 2 billion. This study aims to estimate the prevalence of cognitive impairment and evaluate the association between various socio demographic and behavioural risk factors. Methodology: This descriptive cross-sectional study was carried among 330 senior citizens living in old age homes by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study using the Bims scale (brief interview for mental state) done among elders in Chengalpattu, Tamilnadu by Sujitha P et al found that nearly 44% had mild-moderate cognitive impairment, and 36% had severe cognitive impairment. Only 20% of the respondents had intact cognitive levels [19] where as in our study when graded (according to the moca B scale)13%,42 elders had severe cognitive impairment,54.1%,171 had moderate and 28.2%,89 had mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 58%
“…A study using the Bims scale (brief interview for mental state) done among elders in Chengalpattu, Tamilnadu by Sujitha P et al found that nearly 44% had mild-moderate cognitive impairment, and 36% had severe cognitive impairment. Only 20% of the respondents had intact cognitive levels [19] where as in our study when graded (according to the moca B scale)13%,42 elders had severe cognitive impairment,54.1%,171 had moderate and 28.2%,89 had mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 58%